Combined Src/EGFR Inhibition Targets STAT3 Signaling and Induces Stromal Remodeling to Improve Survival in Pancreatic Cancer - Dosch, Austin R; Dai, Xizi; Reyzer, Michelle L; Mehra, Siddharth; Srinivasan, Supriya; Willobee, Brent A; Kwon, Deukwoo; Kashikar, Nilesh; Caprioli, Richard; Merchant, Nipun B; Nagathihalli, Nagaraj S (Molecular cancer research, 2020)
Lack of durable response to cytotoxic chemotherapy is a major contributor to the dismal outcomes seen in pancreatic ductal adenocarcinoma (PDAC). Extensive tumor desmoplasia and poor vascular supply are two predominant characteristics which hinder the delivery of chemotherapeutic drugs into PDAC tumors and mediate resistance to therapy. Previously, we have shown that STAT3 is a key biomarker of therapeutic resistance to gemcitabine treatment in PDAC, which can be overcome by combined inhibition of the Src and EGFR pathways. Although it is well-established that concurrent EGFR and Src inhibition exert these antineoplastic properties through direct inhibition of mitogenic pathways in tumor cells, the influence of this combined therapy on stromal constituents in PDAC tumors remains unknown. In this study, we demonstrate in both orthotopic tumor xenograft and (PKT) mouse models that concurrent EGFR and Src inhibition abrogates STAT3 activation, increases microvessel density, and prevents tissue fibrosis . Furthermore, the stromal changes induced by parallel EGFR and Src pathway inhibition resulted in improved overall survival in PKT mice when combined with gemcitabine. As a phase I clinical trial utilizing concurrent EGFR and Src inhibition with gemcitabine has recently concluded, these data provide timely translational insight into the novel mechanism of action of this regimen and expand our understanding into the phenomenon of stromal-mediated therapeutic resistance. IMPLICATIONS: These findings demonstrate that Src/EGFR inhibition targets STAT3, remodels the tumor stroma, and results in enhanced delivery of gemcitabine to improve overall survival in a mouse model of PDAC.